Baseline and Post Exercise Electrocardiography in Brachycephalic Dogs - Tarelho, Bruno Basílio; Garcia Youssef, Amanda; Maingué, Ana Paula; Benedito, Geovanna Santana; Eugênio Luz, Patrick; Gava, Fábio Nelson (Acta Scientiae Veterinariae, 2023)
Background: The brachycephalic dog breeds have been increasing in Brazil, and these animals are predisposed to present the brachycephalic dog syndrome, consisting of anatomical defects that lead to physiological changes and clinical signs such as wheezing, dyspnea, and hypoxia. Electrocardiography (ECG) is a simple test that can detect disturbances in the electrical activity of the heart, including changes present in hypoxia. The brachycephalic dog syndrome can lead to pulmonary hypertension due to hypoxia. Based on this, the present work aimed to evaluate the ECG of brachycephalic dogs in search of significant changes in heart rhythm, ECG waves, and cardiac axis. Materials, Methods & Results: Twenty-nine dogs were evaluated in this study, 19 brachycephalic and 10 mesaticephalic, after approval by an ethics committee the animals were selected. Electrocardiographic examinations were performed in 2 stages, at rest and immediately after a 3-min trot. The exam was performed with a computerized electrocardiograph, with a standard time of 5 min. The standard positioning for performing the examination was the right lateral decubitus position. To improve the electrical conductivity, 70% alcohol was used between the animal’s skin and the electrodes. In statistical analysis, paired t test was performed for comparison of the same group before and after exercise and unpaired t test between groups at the same moments, considering P < 0.05 as significant. Nineteen brachycephalic animals were evaluated, 10 Pugs and 9 French Bulldogs, 9 males and 10 females. The mean age was 3.4 ± 1.8 years; and the mean weight was 12.5 kg ± 2.7 kg. In the control group, consisting of ten mesaticephalic animals, all were non-breed, three males and seven females; the mean age and weight in this group were 4.4 ± 1.5 years and 7.5 kg ± 0.5 kg, respectively. There was a significant increase in heart rate (bpm) after exercise in brachycephalic dogs (baseline: 119.3 ± 4.3; after exercise: 135.1 ± 4.9; P = 0.0005). The same occurred for P wave amplitude (mV) (baseline: 0.20 ± 0.01; after exercise: 0.22 ± 0.01; P = 0.0001). These differences were not found in the control group. There were no alterations in the duration of the P wave, PR interval, QRS complex, and QT interval, and all were within normal values for the species in both groups. The R-wave amplitude remained unaltered and within normal values in both the control and brachycephalic groups. Discussion: The elevation in heart rate may be associated with the chemoreflex secondary to the increased demand for oxygenation during exercise and the hypoxia generated by it. The increase in P amplitude suggests right atrial overload. The P wave corresponds to the atrial depolarization and its amplitude corresponds to the electrical activity in the right atrium. Thus, it is possible to relate the increase in P amplitude and heart rate to the hypoxia caused by exercise in brachycephalic, since this hypoxia results in chemoreceptor activation that increases chronotropism and heart rate. Also, there may be increased pressure in the pulmonary trunk, this increased pressure occurs due to vasoconstriction generated as a reflex to hypoxia in the pulmonary alveoli, leading to a possible picture of acute pulmonary hypertension that, in a cascade effect, leads to hypertrophy and dilation of the right ventricle, increased strength of contractility and ejection affecting the tricuspid valve causing a reflux and consequent overload of the right atrium. Keywords: hypoxia; pulmonary hypertension, brachycephalic. Título: Eletrocardiografia basal e após exercício em cães braquicefálicos. Descritores: hipóxia; hipertensão pulmonar, braquicefálico.